Efficacy of ethanolic seed extracts of Annona spp. against Aphis glycines - Lopes Baldin, Edson Luiz [UNESP]; Soares, Muriel Cicatti Emanoeli [UNESP]; da Silva Santana, Alisson [UNESP]; Hunt, Thomas Elliot; McMechan, Justin; Vélez Arango, Ana Maria; Louis, Joe (Elsevier, 2023)
Soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae), is an important pest that can cause significant economic damage to soybean. Synthetic insecticides are currently employed as the main management strategy to control A. glycines; however, over-use of these products has stimulated research in the development of alternative management methods, including botanical derivatives. In this study, we evaluated the bioactivity of Annona mucosa and A. muricata seed extracts and a formulation based on acetogenins (Anosom® 1 EC, 10,000 ppm) compared to the pyrethroid insecticide lambda-cyhalothrin (Warrior II®) on A. glycines. Initially, the insecticidal effect was assessed in vial bioassays and the concentration-response curves were estimated (LC50/LC90 for A. muricata 305.721 ppm/1290.3 ppm and A. mucosa 134.229 ppm/487.890 ppm, respectively). In the systemic effect bioassay, the same extracts were used (at 100, 500, 1,000, 5000 and 10,000 ppm), showing a reduction in the number of insects on the trifoliates. Both extracts at LC50 and LC90 were used in a behavior test, indicating that they are repellent and Warrior II® was attractive for the insects. The LC90 rates were also used in lethal time (LT) and in greenhouse bioassays. The LT50 for A. mucosa and A. muricata extracts was around 20 h. All treatments showed insect mortality rates above 65%, reaching 100% for Warrior II®, followed by the LC90 of A. mucosa (92.1%). The results demonstrate the potential of Annona spp. derivatives for the management of A. glycines in soybean, and these Annonaceae-derived seed extracts could likely serve as an additional IPM tool to improve A. glycines control strategies in organic farming systems.
Keywords: Acetogenins; Allelochemicals; Botanical derivatives; Soybean aphid